2023
DOI: 10.1039/d2ce01711c
|View full text |Cite
|
Sign up to set email alerts
|

Halogen bond and polymorphism in trans-bis(2-iodo-5-halopyridine)dihalocopper(ii) complexes: crystallographic, theoretical and magnetic studies

Abstract: The effect of halogen bonding interactions on polymorphism in Cu(2I5YP)2X2 has been investigated, where 2I5YP = 2-iodo-5-halopyridine, Y = Br or Cl and X = Cl or Br; these complexes...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…An intramolecular chalcogen bond was found to control the geometry of substituted phenyl-SF 3 molecules. 52 A very recent study 53 showed how an internal XB controls the equilibrium between syn and anti conformers of trans-bis(2iodo-5-halopyridine)dihalocopper(II). Somewhat less explored to this point is the manner in which these same sorts of bonds affect the dynamics of the interconversion between structures of competing stabilities.…”
Section: ■ Introductionmentioning
confidence: 99%
“…An intramolecular chalcogen bond was found to control the geometry of substituted phenyl-SF 3 molecules. 52 A very recent study 53 showed how an internal XB controls the equilibrium between syn and anti conformers of trans-bis(2iodo-5-halopyridine)dihalocopper(II). Somewhat less explored to this point is the manner in which these same sorts of bonds affect the dynamics of the interconversion between structures of competing stabilities.…”
Section: ■ Introductionmentioning
confidence: 99%